The effect of administrative burden on state safety‐net participation: Evidence from food assistance, cash assistance, and Medicaid. - Fox, Ashley; Feng, Wenhui; Reynolds, Megan (Public Administration Review, 2023)
Administrative burden in social welfare programs is increasingly recognized as a barrier to eligible individuals' access to their legally entitled benefits. Using composite indices of administrative rules for three major safety‐net programs (Temporary Assistance to Needy Families, Supplemental Nutrition Assistance Program, and Medicaid) that vary in the degree and type of costs conferred on claimants across states between 2000 and 2016, we examine the effect of rule burden on program participation using two‐way fixed effects models. We find that each program contained numerous rules that confer a high degree of learning and compliance costs, and psychological costs to a lesser extent, though to varying degrees. Reducing costs associated with burdensome administrative rules was associated with higher program inclusivity across the programs, with relaxing some rules contributing more than others. Rules that automate enrollment/renewal, link eligibility with other programs and reduce asset tests seem especially promising. Easing burdensome administrative rules can increase access to services to which claimants are legally entitled.